Burnout in Cardiovascular Care: Prevention Through Job Demands-Resources Theory - Bakker, Arnold B.; Demerouti, Evangelia; Siu, Oi Ling (Elsevier, 2026)
Burnout is a significant concern in cardiology, impacting both healthcare professionals and patient outcomes. Chronic job stress contributes to increased cardiovascular risk by disrupting autonomic regulation, increasing inflammation, and exacerbating metabolic disturbances. Burnout also impairs clinical performance, leading to higher rates of medical errors, reduced diagnostic accuracy, and poorer patient safety. Using Job Demands-Resources (JD-R) theory, this review explains how high job demands and insufficient job and personal resources create a self-reinforcing loss cycle, where burnout fuels self-undermining behaviors that further increase stress. Strategies to prevent burnout include job redesign, recovery interventions, and job crafting to optimize workload and enhance resources.
Keywords: Burnout; Stress; Cardiovascular health; Job crafting; Job Demands-Resources theory; Patient safety; fi=Henkilöstöjohtaminen|en=Human Resource Management|